Mitogenomics of Perumytilus purpuratus (Bivalvia: Mytilidae) and its implications for doubly uniparental inheritance of mitochondria - Smietanka, Beata; Lubosny, Marek; Przylucka, Aleksandra; Gerard, Karin Francoise; Burzynski, Artur (My University, 2018)
Animal mitochondria are usually inherited through the maternal lineage. The exceptional system allowing fathers to transmit their mitochondria to the offspring exists in some bivalves. Its taxonomic spread is poorly understood and new mitogenomic data are needed to fill the gap. Here, we present for the first time the two divergent mitogenomes from Chilean mussel Perumytilus purpuratus. The existence of these sex-specific mitogenomes confirms that this species has the doubly uniparental inheritance (DUI) of mitochondria. The genetic distance between the two mitochondrial lineages in P. purpuratus is not only much bigger than in the Mytilus edulis species complex but also greater than the distance observed in Musculista senhousia, the only other DUI-positive member of the Mytilidae family for which both complete mitochondrial genomes were published to date. One additional, long ORF (open reading frame) is present exclusively in the maternal mitogenome of P. purpuratus. This ORF evolves under purifying selection, and will likely be a target for future DUI research.
Keywords: dui; mtdna